Chemical Composition and Biological Activities of Essential Oil of Thymus haussknechtii Velen. from Turkey - Arabaci, Turan; Özgül, Onur; Içen, Mehmet Sina; Açari, I. Karaca; Balcioglu, Sevgi; Gürhan, Ismet (Asian Journal of Chemistry, 2015)
The genus Thymus L. is represented by 40 species (42 taxa) in Turkey, of which 18 are endemic. Thymus haussknechtii Velen. is endemic species of the genus. In this study, the essential oil of Thymus haussknechtii, obtained by hydrodistillation from the aerial parts, were analyzed by GC/MS. The main constituents of the oils are identified and antioxidant and antibacterial bioassays were determined. Isoborneol (9.06 %), linalool (8.44 %), a-pinene (6.45 %), g-terpinene (6.08 %), camphene (5.12 %), caryophylleneoxide (5.11 %) are established as the major components of the essential oil. The antibacterial activity was evaluated against Escherichia coli ATCC 25922 and Staphylococcus aureus ATCC 29213. Both tested bacteria were inhibited by the essential oil. The essential oil of the species was subjected to a screening for their possible antioxidant activities by using 2,2-diphenyl-1-picrylhydrazyl (DPPH) and ABTS. A remarkable antioxidant activity was observed from the essential oil according to the comparison with the antioxidative potentials of the standard compound used in this study. The findings of the analyzed taxa are compared with the results of previous studies.